Chest Tube Drainage Devices - Toth, Jennifer W.; Reed, Michael F.; Ventola, Lauren K. (Seminars in Respiratory and Critical Care Medicine, 2019)
Placement of a chest tube drains intrapleural fluid and air. The tube should be attached to a drainage system, such as one-, two-, or three-compartment devices, a one-way (Heimlich) valve for ambulatory drainage, a digital system, or a vacuum bottle. The frequently employed three-compartment systems, currently integrated disposable units, allow adjustment of negative pressure or no suction (water seal), and include an air leak meter on the water seal chamber to be used for demonstrating and quantifying air leak. These readings are subjective and prone to interobserver variability. Digital pleural drainage systems offer the benefits of quantification of any air leak and pleural pressure. Indwelling pleural catheters, typically utilized for malignant pleural effusion, can be drained using vacuum bottles. Knowledge of the design and functionality of each device in the setting of an individual patient's specific pleural process facilitates the selection of practical and financially prudent chest tube drainage strategies.
Keywords: chest tube; pleural drainage system; digital drainage systems; tube thoracostomy; pleural catheters; air leak; pleural effusion